Challenges in Implementing Academic Accreditation in Higher Education in Saudi Arabia - Nidal Addas, Abdullah (Journal of King Abdulaziz University: Environmental Design Sciences, 2021)
Higher education standards in Saudi Arabia are changing rapidly to align with the country’s 2030 vision. There is recognition of the importance of education and a clear focus on the quality of education in the objectives of the country’s National Transformation Programs which aim to realize that vision. In this regard, the Ministry of Education (MOE) advises universities to obtain both institutional and program accreditation through the National Commission for Academic Accreditation and Assessment (NCAAA), an autonomous body that reports directly to the Council of Higher Education. The recent demand for program accreditation in Saudi universities revealed a lack of enthusiasm among faculty members because of the accreditation process. The Bachelor of Landscape Architecture (BLA) program at King Abdulaziz University began the process in 2017. Using the program as a case study, this paper outlines the process and its requirements. In addition, the paper emphasizes the challenges faced during the process, which include a lack of understanding and awareness, as well as resistance to change. The methodology included the actual process for the BLA program, with observation and unstructured interviews with faculty members. The main findings indicate the importance of academic accreditation when it is considered as a tool for enhancing education and program quality, rather than just being additional paperwork and written procedures that are not implemented. Two years after implementing the NCAAA standard to enhance the quality of the program, there have been clear improvements in program administration, course delivery and quality. It is evident that there is a need for real commitment and belief in the value of accreditation from all faculty members if improvements are to be achieved. It is recommended that the NCAAA helps by developing the accreditation process to make it easier to follow.